2010
DOI: 10.1002/adma.201004052
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Optoelectronic Nose with Nanostructured Wavelength‐Scalable Hollow‐Core Infrared Fibers

Abstract: Cataloged from PDF version of article.A digital photonic nose concept based on infrared absorption inside a hollow core infrared-transmitting fi ber array is presented. Wavelength- scalable photonic bandgap fi bers fi lter specifi c energy photons from a blackbody source, where volatile compounds selectively absorb photons depending on their chemical absorption spectrum. The pattern resulting in the detector array is processed as a binary signature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…On the other hand, samples spiked with 5% alcohol resulted in a significant decrease in the fiber transmissions, which is in good accordance with the results of alcohol water mixture experiments. As we previously reported, 27 the sensitivity of the optoelectronic nose is around low parts per million (ppm) levels (comparable with the sensitivity of FT-IR spectroscopy) since a blackbody light source was used in the optoelectronic nose design. The sensitivity of the nose is not high enough to smell the volatiles in these beverages, which might have concentrations in the vapor phase lower than 1 ppm.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…On the other hand, samples spiked with 5% alcohol resulted in a significant decrease in the fiber transmissions, which is in good accordance with the results of alcohol water mixture experiments. As we previously reported, 27 the sensitivity of the optoelectronic nose is around low parts per million (ppm) levels (comparable with the sensitivity of FT-IR spectroscopy) since a blackbody light source was used in the optoelectronic nose design. The sensitivity of the nose is not high enough to smell the volatiles in these beverages, which might have concentrations in the vapor phase lower than 1 ppm.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Therefore, the extra fibers can be selected appropriately to differentiate more chemicals; for example, we recently showed that six fibers can be easily used to resolve 10 chemicals. 21 The suitable choice of a threshold value results in a unique binary fingerprint for each chemical in the measurement data set. It is essential to note that the threshold value should be wider than the standard deviation of the experimental error in the quenching values to accommodate experimental noise; that is, the binary representation for each chemical should remain unchanged due to the signal noise.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21 Such design enables detection of any infrared absorbing chemical based on the detection of its infrared absorption pattern by spanning the whole spectrum with the sensing fiber array. The specialty PBG fibers are produced, by controlling fiber drawing parameters, to guide a specified spectral band from the whole infrared spectrum relevant to organic molecules.…”
mentioning
confidence: 99%
“…[29][30][31][32] This simple and robust manufacturing process enables to maintain well defi ned material geometries along the length of the fi ber. In this work, we utilized fi ber drawing method to modify fi ber surface morphology in order to obtain enhanced anisotropic wetting on fi ber surfaces.…”
Section: Fabrication Of Textured Fibersmentioning
confidence: 99%